Selection of stock funds using information that is not observable or measurable - Amaral, Rodrigo Coccarelli Marroco do; Leal, Ricardo Pereira Câmara (Revista Contabilidade & Finanças, 2023)
The aim of this paper is to investigate whether the flows and the future returns of stock funds are related to investors’ unobservable information. This article extends the knowledge about investment decisions regarding stock funds and considers a representation of unobservable information that until now has not been contemplated by the Brazilian literature. Understanding decisions to invest in stocks has become more important since the fall in interest rates and migration toward equity investments. The use of unobservable information for making investment decisions is important when choosing stock funds and the return gap could be added to the list of information offered to investors. The return gap measures the value added by managers in relation to the most recently disclosed complete lagged portfolio and was calculated every month for every asset in the portfolios of every fund in the sample disclosed with a three-month lag. A parsimonious sample was used of 22 actively managed funds in the period from January of 2010 to December of 2018, containing one from every one of the 22 biggest independent Brazilian managers, because it is laborious to calculate this metric. The return gap represents unobservable information about a fund. Investors that direct their capital toward stock funds with a higher historical return gap tend to obtain higher returns in out-of-sample tests, suggesting persistence of the returns of these funds and supporting the importance of unobservable information. Investors that directed their capital toward funds with lower historical return gaps could also obtain positive alphas in some cases, indicating that some managers were neglected. The fund flow results were inconclusive.